Extension of Mitogenome Enrichment Based on Single Long-Range PCR: mtDNAs and Putative Mitochondrial-Derived Peptides of Five Rodent Hibernators - Emser, Sarah V.; Schaschl, Helmut; Millesi, Eva; Steinborn, Ralf (Frontiers in Genetics, 2021)
Enriching mitochondrial DNA (mtDNA) for whole mitogenome sequencing achieved for example by amplification of the entire mitogenome in a single PCR, avoids interference from the omnipresent nuclear mtDNA sequences (NUMTs). The approach is currently restricted to the use of samples collected from humans or ray-finned fishes. Here, we relaxed this limitation by introducing a pan-vertebrate assay for mitogenome sequencing that is also based on a single long-range PCR primed with two back-to-back oligonucleotides. The assay was exemplarily applied to five hibernating rodents, namely alpine marmot, Arctic and European ground squirrels, and common and garden dormice, four of which have not been completely sequenced before. The assay requiring intact mitochondrial rings can be used to study novel mitogenomes, mitotypes of a population and mitochondrial heteroplasmy in a straightforward, sensitive and flexible manner. The analysis of the novel mitogenomes addressed amino acid changes of the OXPHOS complexes that were formerly related to cold-adaptation. No obvious pattern was found for the diverse sets of vertebrate species that either apply daily or multiple torpor or otherwise cope with cold. The prediction of small mitochondrial open reading frames (sORFs) encoded by the novel mitogenomes of this study revealed three highly conserved mitochondrial-derived peptides (MDPs), MOTs-c, SHLP4 and SHLP6. While their lengths were moderately conserved, highly homologous segments were identified. A nucleotide substitution in the MT-RNR2 gene causing reduction of the predicted SHLP6 size from 20 to nine amino acids was negatively associated with torpor-free cold adaptation (p = 0.006). The high evolutionary or physiological constraints suggested by sequence conservation of SHLP4 and 6 request future experimentation.